Phosphatidylinositol 4,5-Bisphosphate Reverses Endothelin-1–Induced Insulin Resistance via an Actin-Dependent Mechanism - Strawbridge, Andrew B. (2005)
Phosphatidylinositol (PI) 4,5-bisphosphate (PIP(2)) plays a pivotal role in insulin-stimulated glucose transport as an important precursor to PI 3,4,5-trisphosphate (PIP(3)) and a key regulator of actin polymerization. Since endothelin (ET)-1 impairs insulin sensitivity and PIP(2) is a target of ET-1–induced signaling, we tested whether a change in insulin-stimulated PIP(3) generation and signaling, PIP(2)-regulated actin polymerization, or a combination of both accounted for ET-1–induced insulin resistance. Concomitant with a time-dependent loss of insulin sensitivity, ET-1 caused a parallel reduction in plasma membrane PIP(2). Despite decreased insulin-stimulated PI 3-kinase activity and PIP(3) generation, ET-1 did not diminish downstream signaling to Akt-2. Furthermore, addition of exogenous PIP(2), but not PIP(3), restored insulin-regulated GLUT4 translocation and glucose transport impaired by ET-1. Microscopic and biochemical analyses revealed a PIP(2)-dependent loss of cortical filamentous actin (F-actin) in ET-1–treated cells. Restoration of insulin sensitivity by PIP(2) add-back occurred concomitant with a reestablishment of cortical F-actin. The corrective effect of exogenous PIP(2) in ET-1–induced insulin-resistant cells was not present in cells where cortical F-actin remained experimentally depolymerized. These data suggest that ET-1–induced insulin resistance results from reversible changes in PIP(2)-regulated actin polymerization and not PIP(2)-dependent signaling.